Femur bone repair in ovariectomized rats under the local action of alendronate, hydroxyapatite and the association of alendronate and hydroxyapatite - Victor Canettieri, Antonio Carlos [UNESP]; Dias Colombo, Carlos Eduardo [UNESP]; Chin, Chung Man [UNESP]; Faig-Leite, Horacio [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>An evaluation was made of the local action of alendronate sodium (A), hydroxyapatite (HA) and the association of both substances (A + HA), in different molar concentrations, on the femur bone repair of ovariectomized rats. Ninety-eight animals were divided into seven groups: control (C), starch (S), alendronate 1 mol (A1), alendronate 2 mols (A2), hydroxyapatite 1 mol (HA1), hydroxyapatite 2 mols (HA2) and the association of alendronate + hydroxyapatite (A + HA). Rats weighing about 250 g were ovariectomized and 2.5-mm diameter bone defects were made on the left femur 30 days later. Each experimental group had defects filled with appropriate material, except for group C (control). The animals were killed 7 and 21 days after surgery. Histological, histomorphometric and statistical analyses of bone neoformation in the bone defect site were performed. From the histological standpoint, the major differences occurred after 21 days. All specimens in groups C, S, HA1 and HA2 presented linear closure of the bone defect, and most animals in groups A1, A2 and A + HA showed no bone neoformation in the central area of the defect. No statistically significant difference was found among the experimental groups after 7 days; after 21 days, group HA2 presented the highest amount of neoformed bone. There was no significant difference among groups A1, A2 and A + HA in the two study periods. It was concluded that alendronate, either isolated or in association with hydroxyapatite, had an adverse effect on bone repair in this experimental model. Moreover, the hydroxyapatite used here proved to be biocompatible and osteoconductive, with group HA2 showing the best results.
Keywords: alendronate; bisphosphonates; bone repair; histomorphometry; hydroxyapatite; rats